PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMICS ORDER QUANTITY (Studi pada Kampung Coklat Blitar) - Larasati, Neny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research performed cause of the raw materials inventory control is not use any specific methods. As a result the company has too often make an order of raw materials, so that the ordering cost is not yet under control. The Raw material costs can be minimized by implementing Economics Order Quantity (EOQ) methods. This method can show economical quantity order, economical order frequency, and the time for make Re-Order Point (ROP).This research aims to know the raw material inventory control process with the actual conditions of the company and the influence of implementing EOQ method to the total of raw materials inventory costs. Data collection is carried out by means of observation and interviews, while the analysis tool use the formulation of EOQ, ROP, the ordering frequency and Total Cost (TC).The result of this research show that the total cost of the inventory of raw materials by using EOQ method showed lower numbers. This occurs due to the reduced frequency of ordering raw materials.Keywords: Inventory Control, Raw Materials Inventory, EOQ, ROP, Inventory Cost, Ordering Cost, Storage Costs, Total Cost.